1990
DOI: 10.1086/208558
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Time in the Action of the Consumer

Abstract: A phenomenological approach was used to study the temporal system of consumers, an important but neglected aspect of individual action and consumer behavior. Two patterns of temporal attitude with profoundly different implications for consumer behavior were identified: some individuals appear to live and act as if they are more subject to deterministic functioning in relation to their temporal orientation, while others appear subject to voluntaristic functioning. Different temporal orientations may induce diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
201
0
31

Year Published

1996
1996
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 273 publications
(233 citation statements)
references
References 47 publications
1
201
0
31
Order By: Relevance
“…In an earlier research on the role of time in individuals' actions, I have suggested challenging the hegemonic concept of an arrow of time PPF use to support human action (Bergadaà, 1990). We endorsed Schütz' perspective (1970) that is based on everyday experience, the meaning it bears for the individual and a reality rooted in the relation with its environment.…”
Section: The Arrow Of Time: Past-present-futurementioning
confidence: 83%
See 2 more Smart Citations
“…In an earlier research on the role of time in individuals' actions, I have suggested challenging the hegemonic concept of an arrow of time PPF use to support human action (Bergadaà, 1990). We endorsed Schütz' perspective (1970) that is based on everyday experience, the meaning it bears for the individual and a reality rooted in the relation with its environment.…”
Section: The Arrow Of Time: Past-present-futurementioning
confidence: 83%
“…We endorsed Schütz' perspective (1970) that is based on everyday experience, the meaning it bears for the individual and a reality rooted in the relation with its environment. We found that individuals think of themselves as either 'actors' or 'reactors' with regard to temporality (Bergadaà, 1990). The difference was that the reactors acted in order to do or to achieve, because planning is reassuring to them.…”
Section: The Arrow Of Time: Past-present-futurementioning
confidence: 87%
See 1 more Smart Citation
“…b) Pour chacune des propositions induites de cette première analyse des indices discriminants ont été définis comme étant susceptibles de réunir les propositions ou de les différencier clairement. Cette analyse inductive a permis de dégager une structuration du phénomène tel que vécu au quotidien par les dirigeants interviewés (Lincoln et Guba, 1985;Belk, Sherry, Wallendork, 1988 ;Bergadaà, 1990). A ce stade la dynamique de chacun des quatre principaux portraits est apparue, articulée autour des trois questions de recherche.…”
Section: Analyse De Contenuunclassified
“…Individuals who, on the contrary, make no projects and think that they are subject to the shifts of fortune are more aware of the recreational value of the objects that surround them (Bergadaà, 1988).…”
mentioning
confidence: 99%